Post Burn Depression - NADIA AZAD, FARKHANDA JABEEN, NADEEM ABBAS, SHAHID MAHMOOD, (Journal of Fatima Jinnah Medical University, 2018)
Introduction: With increasing survival rate after severe extensive burns, there is growing interest in the physical and psychosocial outcomes after burns. Studies have indicated high rates of depression, anxiety and post traumatic stress disorder. Objectives: To determine the frequency of depression in post burn patients. Material & Methods: It is a cross sectional study. Patients admitted with burn injury at Fauji Foundation hospital Rawalpindi were included in the study. Data over the period of 2 years was collected and analyzed. Severity of depression was evaluated with Beck Depressive Inventory. Results: This study included ninety four patients. In only one patient, there was history of depression previously. Mean age was 31.31±15.3 years and 70 % of the patients were females. On evaluation 39.4% had mild depression and 16% had moderate depression. Only one patient had severe depression. Female gender was significantly associated with post burn depression. Area of residence, marital status and patient’s occupation were not significantly related with depression in burn patients. Similarly cause of burn and extent of burn did not show statistically significant (p 0.36) association with depression. Conclusions: High frequency of depression in patients with burns call for the increased vigilance on part of the treating team to ensure that depression is recognized and treated. For better management of patients with burns, we also need to employ the social workers, vocational counselors and psychologists in addition to surgeons as part of the multidisciplinary burn team.